Nutritional Potential of Berlandier Nettle Spurge (Jatropha cathartica) Seed - Oladele, P. Ebun-Oluwa; Oshodi, A. Aladesanmi (Pakistan Journal of Nutrition, 2007)
The proximate composition, mineral content and some antinutritional components of Jatropha cathartica seed were studied. Proximate analysis showed that Jatropha cathartica contains 2.53% moisture, 47.13% crude fat, 1.60% crude fibre, 38.50% crude protein, 6.32% ash 6.45% carbohydrate. The seeds are rich in various minerals with highest values occurring for Nitrogen (6.16%), Phosphorus (2.13%) Magnesium (1.03%) and Potassium (0.99%). Copper and Nickel were not detected in the sample. The seeds contain 2.95% and 0.41% phytate and tannin respectively. It could therefore be inferred that the seeds of Jatropha cathartica is nutritionally promising because of its high nutrient content and low antinutrient level.